2007
DOI: 10.1095/biolreprod.106.059261
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Aquaporin 3 in the Movement of Water and Cryoprotectants in Mouse Morulae1

Abstract: The permeability to water and cryoprotectants of the plasma membrane is crucial to the successful cryopreservation of embryos. Previously, we have shown in mouse morulae that water and glycerol move across the plasma membrane by facilitated diffusion, and we have suggested that aquaporin 3 plays an important role in their movement. In the present study, we clarify the contribution of aquaporin 3 to the movement of water and various cryoprotectants in mouse morulae by measuring the Arrhenius activation energies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 21 publications
4
45
0
Order By: Relevance
“…AQP3 was demonstrated to mediate water and cryoprotectant movement and regulated embryo apoptosis during embryo cryopreservation [18,19,20,21]. In the present study, we demonstrated expression of AQP3 and AQP7 mRNAs and proteins in mouse oocytes and preimplantation embryos at all stages.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…AQP3 was demonstrated to mediate water and cryoprotectant movement and regulated embryo apoptosis during embryo cryopreservation [18,19,20,21]. In the present study, we demonstrated expression of AQP3 and AQP7 mRNAs and proteins in mouse oocytes and preimplantation embryos at all stages.…”
Section: Discussionsupporting
confidence: 64%
“…Down-regulation of AQP3 has been shown to be involved in impaired function of several cell types including oocytes, embryos and somatic cells. Knockout of AQP3 in mouse zygotes significantly decreased water and cryoprotectant permeability [21]. Impaired proliferation of epidermal cells was observed in AQP3 null mice [22].…”
Section: Discussionmentioning
confidence: 99%
“…[27] for mouse oocytes consists of ethylene glycol (EG), acetamide, sucrose, and Ficoll dissolved in isotonic phosphate buffered saline (PB1). The oocyte is highly permeable to EG and acetamide [5,28], but is impermeable to the last three. This composition is typical of vitrification solutions in that it consists of permeable and non-permeable solutes, low and high molecular weight solutes, and has a very high total molality.…”
Section: Resultsmentioning
confidence: 99%
“…Then the left end of the Cryotop holder [3] is pressed manually, tipping the sample out of the LN 2 in the Styrofoam well, releasing the LN 2 cover slide to cover the well, and firing the laser as the slide slips into position. The operational details are as follows: The LN 2 well [5] in the Styrofoam block is filled with LN 2. Then,…”
Section: The Laser the Laser Pulse The Cryo Jig And The Resultant mentioning
confidence: 99%
“…Numerous research articles have focused on CPA permeability and the rate at which it enters cells [5,6]. Other studies have investigated incubation times in both the pretreatment and vitrification solutions and found that the temperature used during the handling procedure is also important for successful vitrification [7-9].…”
Section: Introductionmentioning
confidence: 99%